Flexural Behaviour Of Rubberized Concrete Compared To Normal Reinforced Concrete Rectangular Beam - Susanna Liow, Soo Yee (Universiti Sains Malaysia, 2018)
Due to the health and environmental issue associated with the waste tyre disposal and problem of the natural resources depletion, the effort of incorporating waste tyre rubber particles bring twofold benefits. Most of the researchers investigated the effect of rubber content and the rubber sizes on concrete properties at material level but limited studies carried out to determine the rubberized concrete behaviours at structural level. In this study, two types of tyre rubber, crumb rubber (CR) (1.15-2.36mm) and ground rubber (GR) (0.177mm) and a combination of both are used to replace 20% fine aggregate by volume in concrete. Four reinforced beam specimens including controlled specimens were prepared with the same reinforcement configuration and tested under four point bending test to compare their ultimate flexural strength, deflection at peak load and their cracking pattern. The mechanical properties of the rubberized concrete such as compressive strength and splitting tensile strength were also examined. For the compressive strength and splitting tensile strength test results, both possessed similar trend at which the rubber particle size is inversely proportional to their reduction rate. This means that the concrete mix with small rubber particles experienced a greater loss in strength compare to those with larger rubber particles. The results also indicated that although the ultimate flexural capacity of the beams decreased with the incorporation of rubber particles, the deflection of the beam improved with the inclusion of tyre rubber aggregate. At constant sand volume replacement, reinforced beam contained smaller rubber particles exhibited higher ultimate flexural capacity and achieved a higher maximum deflection at midspan of beam before failure. The beams exhibited almost similar ultimate flexural capacity since this property is governed by the yielding of tensile reinforcement and less influence by the compressive strength.